Proteomic clues to the identification of QX disease-resistance biomarkers in selectively bred Sydney rock oysters, Saccostrea glomerata - Simonian, Margaret; Nair, Sham V.; Nell, John A.; Raftos, David A. (Journal of Proteomics, 2009)
The Sydney rock oyster, Saccostrea glomerata, is susceptible to infection by the protozoan parasite, Marteilia sydneyi, the causative agent of QX disease. M. sydneyi infection peaks during summer when QX disease can cause up to 95% mortality. The current study takes a proteomic approach using 2-dimensional electrophoresis and mass spectrometry to identify markers of QX disease resistance among Sydney rock oysters. Proteome maps were developed for QX disease-resistant and -susceptible oysters. Six proteins in those maps were clearly associated with resistance and so were characterized by mass spectrometry. Two of the proteins (p9 and p11) were homologous to superoxide dismutase-like molecules from the Pacific oyster, Crassostrea gigas, and the Eastern oyster, Crassostrea virginica. The remaining S. glomerata proteins had no obvious similarities to known molecules in sequence databases. p9 and p11 are currently being investigated as potential markers for the selective breeding of QX disease-resistant oysters.